1980
DOI: 10.1111/j.1476-5381.1980.tb10696.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Preparation of Highly Purified Slow Reacting Substance of Anaphylaxis (Srs‐a) From Biological Extracts

Abstract: Very highly purified (> 100,000 u/mg) slow reacting substance of anaphylaxis (SRS‐A) has been prepared by reversed phase high pressure liquid chromatographic (HPLC) techniques. High resolution liquid chromatography suggests that SRS‐A may exist in at least three distinct forms which are possible tautomeric. SRS‐A collected by antigen challenge in vivo and by calcium ionophore‐induced release in vitro are chromatographically indistinguishable. Treatment of SRS‐A with diazomethane but not sodium borohydride resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
1983
1983

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…SRS activity (either from platelets or peritoneal cells) was eluted only with ethanol/concentrated ammonia/water (6:3:1 vol/vol). Furthermore, platelet and peritoneal cell-derived SRS exhibited similar RP-HPLC elution patterns that were identical to those reported for guinea pig lung in (19) (Fig. 2).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…SRS activity (either from platelets or peritoneal cells) was eluted only with ethanol/concentrated ammonia/water (6:3:1 vol/vol). Furthermore, platelet and peritoneal cell-derived SRS exhibited similar RP-HPLC elution patterns that were identical to those reported for guinea pig lung in (19) (Fig. 2).…”
Section: Methodssupporting
confidence: 77%
“…They could be due to storage in deep freeze, an effect that has already been observed (19). However, SRS appears to belong to several molecular species derived from AA (27)(28)(29)(30)(31)(32) (26,35,36).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…These workers have postulated on this evidence that ionophore-induced SRS and possibly immunologicallyinduced SRS-A are metabolites of arachidonic acid. Recent studies in our laboratory have indicated that the slow-reacting substances induced by either stimulus are chromatographically indistinguishable (Blackwell, Burka & Flower, 1978). Therefore, we shall use the term SRS-A so that our results can relate to the classical substance described by Brocklehurst (1960).…”
Section: Introductionmentioning
confidence: 99%